2013
DOI: 10.1371/journal.pone.0053828
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Functional Roles of Chitosan as a Potential Protective Agent against Obesity

Abstract: Chitosan, a natural polysaccharide comprising copolymers of glucosamine and N-acetylglucosamine, has been shown to have anti-obesity properties. Two experiments (Exp. 1 and Exp. 2) were performed to determine the role of chitosan on dietary intake, body weight gain, and fat deposition in a pig model, as well as identifying potential mechanisms underlying the anti-obesity effect of chitosan. In Exp. 1, the nutrient digestibility experiment, 16 pigs (n = 4/treatment) were randomly allocated to one of four dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 43 publications
4
61
1
2
Order By: Relevance
“…This observation is supported by previous study (Walsh et al, 2013). To date the mechanism may be postulated as follows: firstly, chitosan might interrupt enterohepatic bile acid circulation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This observation is supported by previous study (Walsh et al, 2013). To date the mechanism may be postulated as follows: firstly, chitosan might interrupt enterohepatic bile acid circulation.…”
Section: Discussionsupporting
confidence: 88%
“…Tang et al (2005) also reported that chitosan could improve the growth performance and feed efficiency of piglets. However, Razdan et al (1997) observed that dietary supplementation of 30 g/kg chitosan significantly reduced body weights and feed intakes of broiler chickens compared with those fed on control diets on days 5 and 11 of the experiment, and Walsh et al (2013) obtained similar results in pigs. As a possible explanation for these divergences the authors hypothesized that in different experiments different doses of chitosan had been used.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Results from two pilot studies on shrimp-derived glucosamine supplements (Gray et al 2004) and a chitosan bandage (Waibel et al 2011) produced no evidence of allergic reaction in human subjects. Rather, chitosan has been a popular weight management supplement for animals and humans (Walsh et al 2013), which further suggests that chitosan is safe for environmental applications.…”
Section: Properties Of Chitosanmentioning
confidence: 99%
“…Compared with other natural polysaccharides, a plethora of applications of this biopolymer have been found owing to its high biocompatible, biodegradable, and nontoxic nature (Jayakumar et al, 2010;Dash et al, 2011).As a natural cationic polysaccharide, CS contains reactive functional groups, that is, hydroxyl and amino groups. Numerous studies have demonstrated that CS has unique biological activities, which include anti-microbial (Zheng & Zhu, 2003), immunostimulatory (Zaharoff et al, 2007), anti-inflammatory (Villiers et al, 2009), anti-tumour (Qin et al, 2002), anti-hypertension (Park et al, 2009), hypocholesterolemic , anti-obesity (Walsh et al, 2013), and anti-oxidation (Kim & Thomas, 2007) properties. Notably, because of these properties, CS can be used as a pro-growth and health feed supplement for farm animals.…”
Section: Introductionmentioning
confidence: 99%